Improving functional standards of apartments in buildings from large-panels, on the example of solutions applied in Lublin in the 1970s and 1980s of the 20th century - Dmitruk, Michał (Budownictwo i Architektura / Civil and Architectural Engineering, 2022)
Housing blocks constructed from prefabricated elements have been the backbone of housing resources in many Polish cities in the last fifty years. Over the time, the residents’ expectations regarding the residential amenity standards, as well as demographic structure of the estates built in the communist era have changed. Therefore, the current residents’ needs significantly differ from the needs and expectations of those who took over the newly built flats in the last quarter of the 20th century. Fundamentally, the functional and spatial standards of flats built before 1989 are already out of date. The proper functioning of the usable dwelling space of these apartments has gained additional importance due to the inhabitants getting progressively older and, especially recently, the prolonged SARS CoV-2 pandemic. The introduction of the lockdown, which involved strict restrictions on movement outside the place of residence during the pandemic, made the apartments the centre of life and a place of work for many families. Suddenly, for psychophysical reasons, the importance of having larger floor space, than the functional solutions typically used in the 1970s and 1980s offered, has increased. It appears that the residents begun to take interest in all possible solutions to improve the functionality of their homes. The aim of the article is to present proposals for contemporary architectural solutions that can improve the functionality of these apartments that would increase residents’ standard of living and everyday comfort.